Hinge epistemology - Coliva, Annalisa, 1973-; Moyal-Sharrock, Danièle, 1954- (Religious Studies, Theology and Philosophy E-Books Online, Collection 2016, ISBN: 9789004303942., 2016)
In Hinge Epistemology , eminent epistemologists investigate Wittgenstein's concept of basic certainty or 'hinge certainty'. The volume begins by examining the salient features of 'hinges': Are they propositions that enjoy a special kind of non-evidential justification? Are they objects of knowledge or ways of acting mistaken for known propositions? Various attempts are then made to integrate hinges in the development of a viable epistemology: Can they shed light on the conditions of satisfaction for knowledge and justification? Do they offer a solution to scepticism? Finally, the application of hinges is explored in such areas as common knowledge and intellectual loyalty. The volume attests to the importance of hinge certainty and Wittgenstein's On Certainty for mainstream epistemology.